Construction of Microunits by Adipose-Derived Mesenchymal Stem Cells Laden with Porous Microcryogels for Repairing an Acute Achilles Tendon Rupture in a Rat Model - Yang X (Dove Medical Press, 2020)
Xuan Yang,1,2 Haoye Meng,1 Jiang Peng,1 Lijuan Xu,1 Yu Wang,1 Xun Sun,3 Yanxu Zhao,1 Qi Quan,1 Wen Yu,1 Mingxue Chen,1 Tong Shi,2 Yanan Du,4 Shibi Lu,1 Aiyuan Wang1 1Department of Orthopedic Surgery, Key Laboratory of Musculoskeletal Trauma &war Injuries PLA, Beijing Key Laboratory of Regenerative Medicine in Orthopedics, Chinese PLA General Hospital, Beijing 100853, People’s Republic of China; 2Department of orthopedics, The First Hospital of Shanxi Medical University YanHu District Branch, Yuncheng, Shanxi 044000, People’s Republic of China; 3Department of Orthopedics, Tianjin Hospital, Tianjin 300211, People’s Republic of China; 4Department of Biomedical Engineering, School of Medicine, Tsinghua University, Beijing 100084, People’s Republic of ChinaCorrespondence: Aiyuan Wang; Jiang Peng Email aiyuanwang301@126.com; pengjiang301@126.comObjective: Tissue engineering approaches seem to be an attractive therapy for tendon rupture. Novel injectable porous gelatin microcryogels (GMs) can promote cell attachment and proliferation, thus facilitating the repair potential for target tissue regeneration. The research objectives of this study were to assess the efficacy of tissue-like microunits constructed by multiple GMs laden with adipose-derived mesenchymal stem cells (ASCs) in accelerated tendon regeneration in a rat model.Methods: Through a series of experiments, such as isolation and identification of ASCs, scanning electron microscopy, mercury intrusion porosimetry (MIP), laser scanning confocal microscopy and the CCK-8 test, the biocompatibility of GMs was evaluated. In an in vivo study, 64 rat right transected Achilles tendons were randomly divided into four groups: the ASCs+GMs group (microunits aggregated by multiple ASC-laden GMs injected into the gap), the ASCs group (ASCs injected into the gap), the GMs group (GMs injected into the gap) and the blank defect group (non-treated). At 2 and 4 weeks postoperatively, the healing tissue was harvested to evaluate the gross observation and scoring, biomechanical testing, histological staining and quantitative scoring. Gait analysis was performed over time. The 64 rats were randomly assigned into 4 groups: (1) micro-unit group (ASCs+GMs) containing ASC (105)-loaded 120 GMs in 60 μL DMEM; (2) cell control group (ASCs) containing 106 ASCs in 60 μL DMEM; (3) GM control group (GMs) containing 120 blank GMs in 60 μL DMEM; (4) blank defect group (Defect) containing 60 μL DMEM, which were injected into the defect sites. All animals were sacrificed at 2 and 4 weeks postsurgery (Table 1).Results: In an in vitro study, GMs (from 126 μm to 348 μm) showed good porosities and a three-dimensional void structure with a good interpore connectivity of the micropores and exhibited excellent biocompatibility with ASCs. As the culture time elapsed, the extracellular matrix (ECM) secreted by ASCs encased the GMs, bound multiple microspheres together, and then formed active tendon tissue-engineering microunits. In animal experiments, the ASCs+GMs group and the ASCs group showed stimulatory effects on Achilles tendon healing. Moreover, the ASCs+GMs group was the best at improving the macroscopic appearance, histological morphology, Achilles functional index (AFI), and biomechanical properties of repair tissue without causing adverse immune reactions.Conclusion: Porous GMs were conducive to promoting cell proliferation and facilitating ECM secretion. The ASCs-GMs matrices showed an obvious therapeutic efficiency for Achilles tendon rupture in rats.Keywords: Achilles tendon rupture, tendon tissue engineering, adipose-derived mesenchymal stem cells, ASCs, injectable biomaterials